Predicting Life Satisfaction from Age, Affluence, Religion, Educational Attainment, and Perceived Stress - Barruga, Bernard M. (Future Science, 2025)
This study examined whether marital status, educational attainment, perceived stress, religion, age, and affluence predicted faculty members’ life satisfaction at tertiary schools in Masbate during the school year 2020-2021, which was in the COVID-19 pandemic. Dummy variables were used to enable the inclusion of categorical predictors in regression analysis by converting categories into binary values (0 or 1), allowing for quantitative comparisons. In this study, marital status was coded as “married” and “widowed,” with “single” as the reference group; educational attainment with “bachelor's degree holders” as the baseline compared to “master's degree” and “doctorate” holders; and religion as “Catholic” versus “non-Catholic.” These dummy variables quantify life satisfaction differences among groups while minimizing the risk of multicollinearity and controlling for other variables, preserving the validity of the regression model. Age, affluence, and perceived stress were treated as continuous variables. A total of 130 valid responses were analyzed from 156 participants, with 26 cases excluded due to incomplete responses. Participants were recruited through non-random sampling, including the fact that it limited the generalizability of the findings due to the samples may not represent the population of Masbate tertiary schools faculty members. Data collection was conducted both in-person and online using Google Forms, ensuring accessibility despite potential selection biases inherent in the sampling method. Descriptive statistics, correlation analyses, and linear regression were performed. Age and perceived stress were observed to be significant for life satisfaction, while perceived stress had a significant negative association. In contrast, marital status, affluence, educational attainment, and religion did not demonstrate significant predictive value in the regression model. Non-random sampling and reliance on self-reported measures may limit generalizability. The study highlights the importance of stress management and financial well-being in enhancing faculty life satisfaction, particularly during crises like the COVID-19 pandemic. These findings provide a basis for institutional policies aimed at improving faculty support systems and promoting mental health and resilience.